Comparison of the results of active surgical treatment and serial stenting for urolithiasis in pregnant women - P. Yu. Nizin; R. A. Perov; A. A. Nemenov; S. V. Kotov (Вестник урологии)
Introduction. Renal colic during pregnancy is a common cause of pain in the lower back. Currently, with a diagnosed kidney or ureter stone, the standard treatment is serial drainage of the urine tract using an internal ureter stent, with replacement of the drainage before delivery, followed by surgery to remove the stone after delivery.Objective. To study the effectiveness and safety of ureteroscopic interventions in the treatment of urolithiasis in pregnant women in comparison with the method of serial drainage of the upper urinary tract during gestation followed by surgical treatment of urolithiasis 4 weeks after delivery.Materials & methods. The study group consisted of 119 patients with a confirmed diagnosis of urolothiasis using instrumental diagnostic methods and a gestational age up to and including the 27th week. Two groups were formed based on treatment approaches for urolithiasis: group 1 included 59 patients (49.6%) who underwent surgical removal of the stone; group 2 included 60 patients (50.4%) who underwent internal ureteral stent replacement every 4 – 6 weeks prior to delivery and subsequent ureteroscopy There were no significant differences in age, body mass index, or number of pregnancies between the two groups.Results. The frequency of complete stone removal in groups 1 and 2 was 96.6 and 96.7%, respectively. The median amount of time spent on urolithiasis treatment in groups 1 and 2 was 60 [45; 72] and 97 [54; 105] minutes, respectively (p = 0.002). Migration of the ureteral stent in group 2 was observed in 13.3% of cases (p = 0.05). Among group 1 patients who underwent ureteroscopic intervention aimed at stone removal, the incidence of internal drainage dislocation was 3.4%. Encrustation of the ureteral stent in groups 1 and 2 was observed among 2 (3.4%) and 17 (28.3%) patients, respectively (p < 0.001). The bed-day (median time in days spent in hospital for drainage replacement and time of surgical treatment of urolithiasis) in groups 1 and 2 was four and eight days, respectively (p < 0.05). The frequency of natural childbirth in groups 1 and 2 was 81.35% and 55.0%, respectively (p = 0.002).Conclusion. Urolithiasis among pregnant women is a complex multifactorial disease that affects not only the health of the mother, but also the condition of the developing foetus. It is possible to perform surgical treatment with high efficiency and low complication rate, which improves the quality of life.